Evaluation of factors influencing hypertension among adults of South Karnataka - India - H. S., Darshan Kumar; Sasalu, Karthik N.; R., Suresh S. (International Journal of Advances in Medicine, 2019)
Background: Studies have shown that BP is an independent risk factor for CVD. This relationship is independent as well as consistent and continuous. Observations involving more than 1 million individuals have shown that death from both CVD and stroke increases progressively and linearly from BP levels of as low as 115mm systolic and 75 mm diastolic upwards. The increased risks are present in all age groups ranging from 40 to 89 years old. Hence the present study was undertaken to evaluate the factors influencing hypertension among Adults. Methods: In the present study 400 patients both out-patient and in-patients attending Adichuchanagiri Institute of Medical Sciences were evaluated for factors influencing Hypertension and other cardiovascular diseases. The 400 patients were divided into 200 cases who were again divided into categories based on severity of hypertension into stage 1 and stage 2 and duration of <5 years and ≥5 years. Results: A positive correlation was found between the severity of hypertension, the patients who were found to be having stage 2 hypertension had an increase in SUA levels which was statistically significant when compared with those with stage 1 hypertension. Conclusions: With the results based on the study carried out author concluded that there is direct relation between hyperuricemia and hypertension. Also, the study showed that the SUA levels were significantly increased in patients with Stage 2 hypertension as compared with those of stage 1 hypertension, showing that the severity of hypertension also related to the SUA levels.